KORELASI ANTARA UKURAN-UKURAN TUBUH DAN BOBOT BADAN SAPI PERANAKAN ONGOLE BETINA PADA UMUR PASCASAPIH DI KECAMATAN TANJUNGSARI KABUPATEN LAMPUNG SELATAN - Pius Agus Tian Sarwono, Sulastri, M. Dima Iqbal Hamdani dan Akhmad Dakhlan (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
The purpose of this study was to determine the magnitude of the correlation coefficient between body measurements with body weight and a regression formula that describes the relationship between body weight and body measurements, namely body length (X1), shoulder height (X2), and chest girth (X3) of postweaning Ongole Crosbreed cattle. This research was conducted in February until April 2019 in Tanjungsari District, Lampung Selatan Regency. The research method used was survey method. Data collection was using recording data derived from 97 female Ongole Crosbreed cattle aged 6 months in 2017, 2018 and 2019 from 5 groups of farmer in Tanjungsari District. Data were analyzed using correlation and regression. Coefficient of determination was used to find the best regression model. The results showed that the average body weight, body length, shoulder height, and chest girth were 100.62 ± 17.70 kg, 88.62 ± 11.49 cm, 93.50 ± 9.39 cm, and 99 ± 14.20 cm, respectively. The results showed that there was a moderate relationship between body length (0.478) and chest girth (0.432) on body weight, and a low relationship for shoulder height (0.327) to body weight. The results of this study also showed that the three body measurements significantly influenced body weight variation with regression model of Y = 44.803 + 0.636 (X1) - 0.390 (X2) + 0.363 (X3) having the highest determination coefficient (R2 = 0.255). The results of this study concluded that the diversity of body weight of a 6-month-old female Ongole Crosbreed cattle was 25.50% due to body length, shoulder height, and chest girth, while 74.50% was caused by other unknown factors. Keywords : Body weight, Determination coefficient, Correlation, Regression, Body measurements